Investment and investment finance in Europe: Investing in competitiveness - Atanas Kolev; Tanja Tanayama (European Investment Bank (EIB), 2015)
Europe faces a twofold economic challenge. Post crisis, Europe still suffers from weak confidence, with would-be investors across Europe sitting on ample liquidity but afraid to invest, while deleveraging goes on in both the public and private sector. From a structural point of view Europe faces the longlasting challenge of declining productivity and competitiveness, which has made it more vulnerable to economic turmoil, is undermining the recovery and threatens its economic well-being over the longer term. Getting the conditions right for investment to take place and to accelerate the competitivenessenhancing reallocation of resources is crucial for the future of Europe. The EIB's annual economic publication focuses on investment and investment finance in Europe, discussing both cyclical and structural factors. This year's special topic is investing in competitiveness. – – Der Bericht legt dar, wie sich die Krise nach wie vor auf die Investitionen in Sachanlagen und immaterielle Vermögenswerte sowie auf deren Finanzierung auswirkt. Er untersucht außerdem, welche Bedeutung der Wettbewerbsfähigkeit in einem zunehmend offenen und integrierten Weltmarkt zukommt. Dabei werden die wichtigsten Grundsätze analysiert, die einer wettbewerbsorientierten Wirtschaftspolitik zugrunde liegen müssen. In diesen Bericht sind sowohl Studien der EIB-Hauptabteilung Volkswirtschaftliche Analysen als auch die Arbeiten führender Wissenschaftler eingeflossen. Erstellt wurde er für die EIB-Konferenz zu Wirtschaftsfragen 2015.
Keywords: 330; Investitionspolitik; Wettbewerbspolitik; EU-Staaten